International tourism development in vietnam and Malaysia - Nguyen, Van Hiep (VietNam National University - Ho Chi Minh City, 2018)
The book provides valuable information on tourist potentials of the two countries focusing on the two locations: Penang City - a world heritage city recognized by Unesco, and Binh Duong province, a newly and strongly development province of the south Viet Nam. Directions and measures to promote tourist development between provinces and cities of Vietnam and Malaysia are also recomended